Drifting Apart of Transatlantic Security The American Mark on NATO under Barack Obama - Matle, Aylin (Logos Verlag Berlin, 2021)
For the first time, this book examines the comparative impact of the Obama administration on the NATO and defense policies of European allies. Germany, Poland and Turkey serve as case studies to evaluate American policies vis-à-vis NATO Europe. All three are representative for the Alliance in various ways. Thus, the results of this book offer an outlook for NATO Europe and the Alliance as a whole. Despite the fact that all three countries are highly dependent on American security guarantees in theory and practice, the results of this study reveal different national responses. Indeed, the book demonstrates multi-, bi-, and unilateralization attempts in reaction to US engagement in and vis-à-vis NATO Europe. Hence, a better understanding of current developments within the Alliance as well as the basis for the future debate about the transatlantic organisation are provided. Aylin Matlé works for the Konrad-Adenauer-Stiftung e.V.; most recently, she worked for the foundation's Israel office in Jerusalem. Previously, Aylin Matlé was a research associate at the chair of international relations and European politics at the Martin-Luther-Universität Halle-Wittenberg.